Dissolved and Particulate Primary Production and Subsequent Bacterial C Consumption in the Southern East China Sea - Chen, Tzong-Yueh; Lai, Chao-Chen; Shiah, Fuh-Kwo; Gong, Gwo-Ching (Frontiers in Marine Science, 2020)
Dissolved primary production (DPP), particulate primary production (PPP), and the subsequent bacterial production (BP) and respiration (BR) were reported for the first time in the NW Pacific. The study area of the subtropical southern East China Sea covers different water types, including oligotrophic Kuroshio and Taiwan Strait waters, as well as nutrient-rich China coastal and upwelled Kuroshio subsurface waters. On an areal basis, DPP and PPP ranged from 67-1649 and 160-1182 mgC m-2 d-1, respectively, showing high values in the upwelling area. The contribution of DPP to total primary production (percent extracellular release; PER) averaged 40.8+/-12.2%with >50% in the upwelling stations. The BP and BR ranged from 48-245 and 709-2822 mgC m-2 d-1, respectively, showing patterns similar to those of primary production. Bacterial growth efficiency (BGE) averaged 5.7+/-1.4%, representing in the lower end of the global ocean values. Phytoplankton and bacteria were well coupled in the upwelling area, whereas primary production could not sustain the bacterial carbon demand (BCD) at other stations. The slope of the log-log relationship between DPP and PPP was >1, indicating that the microbial loop may receive less organic carbon supply in the future warmer, less productive ocean.